(untitled) (Journal of the Bangladesh Agricultural University, 2014)
Deep placement of super granular urea is very laborious and time consuming work for manually operation. To overcome the human stress and drudgery to place the super granular urea, a low cost manually operated pull type 2- rows granular urea applicator (GUA) was designed and developed in the department of Farm Power and Machinery, Bangladesh Agricultural University, Mymensingh. The performance of machine was done in agronomy field of Bangladesh Agricultural University. The effective field capacity was 0.11 ha/hr at a forward speed of 1.78 km/hr and 78.89 % field efficiency of developed granular urea applicator. The average distance between two dropped granular urea (GU) from left hopper & right hopper were 40.64 cm and 40.89 cm respectively. The average missing rate of GU dropped during field operation was 1.65% for granular urea size of 2.83 gm. The depth of granular urea placement was 7-10 cm in puddle field. The pulling force and draft of the developed applicator were varied between 5-11 kg and 3-6.62 kg respectively. The draft power was 0.027 kW for 55.38 N pulling force at 1.78 km/hr speed. The application rate of the GUA was 170 kg/ha. The results of field and laboratory test of the developed applicator were better in comparison to other models of GUA. The operational cost of the applicator is 390 Tk/ha which is lower than 22.16% of BARI made push type GUA and 53% lower than the manually placement of GU. Average grain yield was highest (5234 kg/ha) when granular urea were applied by the developed applicator and followed by GU applied by BRRI made push type GUA (5213 kg/ha) and GU applied by manually (5209 kg/ha). The highest straw yield (6787 kg/ha) was obtained when GU applied by manually. However the differences of grain yields and straw yields were not significantly difference for applying GU by the applicators and manually operation. The manufacturing cost of the applicator is only Tk.6000. The weight and the drawbar power of the applicator were 15 kg and 0.03 kW respectively. Therefore one person (man or women) is enough to pull the machine. Overall performance of the applicator was found quite satisfactory. For this reason, the applicator may be introduced in Bangladesh to apply super granular urea. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21414 J. Bangladesh Agril. Univ. 12(1): 211-220, June 2014